THE ROLE OF SELF-REWARD IN BOOSTING PERFORMANCE AND MENTAL WELL- BEING FOR REMOTE GENERATION Z WORKERS - Defalia Widamutia; Veithzal Rivai Zainal; Azis Hakim (Adisam Publisher, 2025)
Generation Z, as digital natives, possess unique characteristics that make them susceptible to stress and burnout. This study aims to explore the impact of self- reward on the performance and mental well-being of Generation Z employees working remotely. Specifically, this research investigates how self-reward can serve as an effective coping mechanism for Generation Z in dealing with high job demands and social isolation associated with remote work. Through a qualitative descriptive approach, this study analyzes the subjective experiences of Generation Z employees regarding their characteristics related to the implementation of self-reward. The findings indicate that self-reward not only enhances performance and motivation but also plays a significant role in maintaining emotional balance and reducing stress levels. Additionally, this study identifies the most effective types of self-reward for Generation Z and the factors influencing the success of its implementation. These findings have important implications for organizations in designing more effective employee development and well-being programs.